PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2016) - Dessi Pratiwi, 14.05.52.0024; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2018)
This research is to examine the effect of profitability, leverage, and firm size on tax avoidance. This research is focused on manufacturing companies listed in Bursa Efek Indonesia (BEI) period 2014-2016. Research conducted with the number of observations as many as 51 compenies obtained by purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis.Â The result of analysis shows that profitability and firm size do not have significant on tax avoidance. Leverage has a positive significant on tax avoidance.Keywords: tax avoidance, profitability, leverage, and firm size